1985
DOI: 10.1128/iai.48.3.735-740.1985
|View full text |Cite
|
Sign up to set email alerts
|

A completely synthetic toxoid vaccine containing Escherichia coli heat-stable toxin and antigenic determinants of the heat-labile toxin B subunit

Abstract: The immunodeterminant regions of the Escherichia coli heat-labile toxin B subunit were identified by determining the antigenicity, by using enzyme-linked immunosorbent assays, of synthetically produced peptides corresponding to various segments of its 124-amino-acid sequence. The addition of the 18-amino-acid sequence of heat-stable toxin (ST) to some of these peptides enhanced their B subunit antigenicity. Peptide residues containing the 26 amino acids of B subunit sequence 58 to 83 joined to the 18-amino-aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Recently, Houghten et al (20) reported the stimulation of protective immune responses against both the heat-labile and heat-stable toxins of Escherichia coli by peroral administration of a hybrid peptide containing a 26 amino acid-residue copy of the labile toxin joined in tandem to an 18-residue copy of stable toxin. However, we believe our studies are the first to show that a synthetic hybrid peptide can raise antibodies that promote the phagocytosis and killing of two different bacterial pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Houghten et al (20) reported the stimulation of protective immune responses against both the heat-labile and heat-stable toxins of Escherichia coli by peroral administration of a hybrid peptide containing a 26 amino acid-residue copy of the labile toxin joined in tandem to an 18-residue copy of stable toxin. However, we believe our studies are the first to show that a synthetic hybrid peptide can raise antibodies that promote the phagocytosis and killing of two different bacterial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic copies of the COOH-terminus, 23-35, of the cyanogen bromide-derived fragment 7 (CB7) of type 24 M protein (17), and the NH~-terminus, 1-20, of pep M5 (9) were the same as those used and reported in previous studies (9,10). They are designated S-CB7(23-35)C and S-M5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), respectively. In addition, two hybrid peptides, S-M5(1-20)-S-CB7(23-35)C and S-M5(1-20)-S-CB7 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were synthesized by the solid-phase method of Merrifield (18) as previously described (10).…”
mentioning
confidence: 99%
“…LT-I and CT and their B subunits were described as very strong immunogens which elicit high-titer serum and secretory antibodies when administered into the gut via the oral route in microgram amounts of protein (21,45) or when delivered to the lymphoid tissue by attenuated Salmonella strains (7,8,11). The B subunits of both enterotoxins also enhance the immunogenicity of relatively poor immunogens when mixed or coupled (chemically or genetically) and given orally (13,15,21,31,40,41). Czerkinsky et al (13) demonstrated that intragastric immunization of mice with Streptococcus mutans antigen I/II covalently coupled to the B subunit of CT elicits a significant immune response (mucosal and serum immunoglobulin A [IgA] and IgG), although subclinical doses of free CT were required to obtain the optimal antibody response.…”
mentioning
confidence: 99%
“…When carbodiimides are used in protein modification, reaction conditions can be more easily controlled and side reactions and the formation of undesirable side-products may be effectively suppressed [31]. Examples of successful carbodiimide-mediated conjugations include meningococcal capsular polysaccharide-tetanus toxoid vaccines [32,33] and E. coli enterotoxin vaccines [34]; other work has shown that EDAC toxoids are stable at 4 ° C and highly immunogenic in mice [15]. In view of these findings, such toxoids should be given further consideration for use in human vaccines and a reappraisal of toxoiding reagents for first and second generation acellular pertussis vaccines is long overdue.…”
Section: Discussionmentioning
confidence: 99%